ANALISIS SUDUT KEMIRINGAN OPTIMUM PADA PANEL SURYA DI ROOFTOP GEDUNG FAKULTAS TEKNIK UPN VETERAN JAKARTA - Yuliana Dewi Saputri, (2023)
Solar panels are devices that can convert sunlight energy into electrical energy. The use of solar panels is very useful for reducing dependence on fossil fuels which are increasingly depleting. However, to maximize its use, it is necessary to pay attention to the tilt angle and position of the solar panel itself. This study was conducted to determine the optimum tilt angle of solar panels in the Limo area with the aim of obtaining maximum power output results. The tests carried out were testing four solar panels with different tilt angles and placement directions. Testing was carried out for 14 days to obtain the current and voltage on each solar panel. Through correlation analysis, it is found that the light intensity received by the solar panel correlates in the same direction as the power produced. Thus, if the light intensity increases, the power output also increases. Furthermore, through analysis of mean the testing process produces an optimal power value of 2,077.62 mW on solar panels with a tilt angle of 10° towards the North. This is in accordance with the influence of the azimuth angle of the sun's position as well as the calculations and recommendations provided by the Global Solar Atlas website.